PENINGKATAN KEMAMPUAN SISWA DALAM MENULIS KATA IMBUHAN PE- MENJADI KALIMAT MENGGUNAKAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT - Juniatuz Zulfah; Effy Mulyasari; Eni Kurniasih (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research focuses on the problems found in class V SDN 134 Panorama, where students have not shown maximum results regarding the learning material of pe- affixed words. The average class score indicates a fairly low number, which is 60.3. This is due to the incompatibility of the PBL model applied with the needs of students and the pe- affix material taught. This study focuses on improving students' ability to write pe- affix sentences by applying the Teams Games Tournament type cooperative learning model in class V of SDN 134 Panorama. The methodology implemented is Collaborative Classroom Action Research, which includes planning, implementation, observation and reflection in two cycles, each with two meetings involving 22 learners. The data of this research is presented in a descriptive qualitative design. Based on the results of the study, there was significant progress in the learners' ability to write pe- affixed sentences. After implementing the intervention in one cycle, there was an increase in the learners' average score from 60 to 83.33 in the first cycle, and increased to 90.90 in the second cycle. This finding indicates that the application of the Teams Games Tournament type cooperative learning model succeeded in improving the ability to write pe- affixed sentences of students in class V SDN 134 Panorama.